2022
DOI: 10.1098/rspb.2021.2697
|View full text |Cite
|
Sign up to set email alerts
|

Life-history traits predict responses of wild bees to climate variation

Abstract: Life-history traits, which are physical traits or behaviours that affect growth, survivorship and reproduction, could play an important role in how well organisms respond to environmental change. By looking for trait-based responses within groups, we can gain a mechanistic understanding of why environmental change might favour or penalize certain species over others. We monitored the abundance of at least 154 bee species for 8 consecutive years in a subalpine region of the Rocky Mountains to ask whether bees r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
(118 reference statements)
3
8
0
Order By: Relevance
“…In Berchtesgaden, mean community body size declined in the warmer year, consistent with the predictions derived from theory and the observation that along spatial temperature gradients, body size declines with increasing temperature (Figure 6a). The reduction in community body size over a relatively short time period is in line with a recent study, which studied bee community response to climate variation in eight consecutive years (Pardee et al, 2022). Body size declines can also be observed over longer time scales up to 140 years (Bartomeus et al, 2013; Nooten & Rehan, 2020).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In Berchtesgaden, mean community body size declined in the warmer year, consistent with the predictions derived from theory and the observation that along spatial temperature gradients, body size declines with increasing temperature (Figure 6a). The reduction in community body size over a relatively short time period is in line with a recent study, which studied bee community response to climate variation in eight consecutive years (Pardee et al, 2022). Body size declines can also be observed over longer time scales up to 140 years (Bartomeus et al, 2013; Nooten & Rehan, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…and the observation that along spatial temperature gradients, body size declines with increasing temperature (Figure 6a). The reduction in community body size over a relatively short time period is in line with a recent study, which studied bee community response to climate variation in eight consecutive years (Pardee et al, 2022).…”
Section: Body Size Shifts At Community Levelsupporting
confidence: 87%
“…Understanding which adaptations or life history traits are associated with population increases or decreases over time in some cases could be a better approach to explain species' changes in abundance over time (e.g., Stemkovski et al, 2020 ; Williams et al, 2009 ). However, given that a suite of natural history traits was not associated with the species‐level changes we observed (Table A2 ), it may take more investigation into environmental variable to understand what mechanism may be driving species' population changes over time in our system (Hamblin et al, 2018 ; Ogilvie et al, 2017 ; Pardee et al, 2022 ; Stemkovski et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…In some studies, natural history traits helped explain changes in bee abundance over time or responses to environmental fluctuations (Bartomeus et al, 2013 ; Hamblin et al, 2018 ). For example, Pardee et al ( 2022 ) found that bee body size and nesting strategy impacted species' responses to changing temperature. We found that 6 commonly studied natural history traits did not predict changes in abundance when controlling for phylogeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation